2022
DOI: 10.7554/elife.74664
|View full text |Cite
|
Sign up to set email alerts
|

High spatial resolution analysis using automated indentation mapping differentiates biomechanical properties of normal vs. degenerated articular cartilage in mice

Abstract: Characterizing the biomechanical properties of articular cartilage is crucial to understanding processes of tissue homeostasis vs. degeneration. In mouse models, however, limitations are imposed by their small joint size and thin cartilage surfaces. Here we present a 3D automated surface mapping system and methodology that allows for mechanical characterization of mouse cartilage with high spatial resolution. We performed repeated indentation mappings, followed by cartilage thickness measurement via needle pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…The mechanisms giving cartilage its mechanical resilience involve complex compositional and structural variations across the tissue’s thickness (depth). Several studies [ 1 , 2 , 3 , 4 , 5 ] have demonstrated that such variations are depth-dependent, site-dependent, joint-dependent, age-dependent, and species-dependent. At the compositional level, articular cartilage contains a small number of cells (chondrocytes) surrounded by extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms giving cartilage its mechanical resilience involve complex compositional and structural variations across the tissue’s thickness (depth). Several studies [ 1 , 2 , 3 , 4 , 5 ] have demonstrated that such variations are depth-dependent, site-dependent, joint-dependent, age-dependent, and species-dependent. At the compositional level, articular cartilage contains a small number of cells (chondrocytes) surrounded by extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%